Mælkeribrugets nuværende Stilling og Fremtidsudsigter. Foredrag, d. 16. Februar 1916. - Ellbrecht, G. (Tidsskrift for Landøkonomi, 2018)
Mælkeribrugets nuværende Stilling og Fremtidsudsigter. Foredrag, d. 16. Februar 1916.